Histological study for the development of Humerus and Femoral Bones in pre-hatched Embryos of Racing Pigeons and Japanese Quail - Iftikhar Mohammed Abdul Karim; Ramzi Al-Agele (Diyala Journal for Veterinary Sciences, 2024)
In developmental biology, studying the histological features of avian embryonic skeletal development might provide a reference standard. As a result, the purpose of this study was to determine the time of onset of ossification in femurs and humerous bones, as well as to characterize the most important histological changes found in these bones. This investigation used thirty fertilized eggs for each type of bird from various bird species, such as Japanese quail and racing pigeons. Embryos were collected at 8, 12, 16, and 18 days, based on the incubation time of each bird. Histological analysis of bone tissues was subsequently performed. The current study found that bones of racing pigeons and quails both underwent cartilage ossification on day 8 of incubation. During embryonic development, the ossification of the hindlimb persisted and even increased. The skeletogenesis ordering of ossification differed between the forelimb humerus bone and the hindlimb femour bone, as shown by comparing their calcification patterns. Results demonstrated that racing pigeons' humorous bones calcified more later than quail's embryonic bones. In conclusion, embryonic bone tissue staining and morphological variance analysis showed that the Japanese quail and pigeon embryos developed in different ways, which was linked to their bones growing at different rates during hatching.